2010
DOI: 10.1371/journal.pntd.0000730
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic and Antitumor Effects of Trypanosoma cruzi Calreticulin

Abstract: BackgroundIn Latin America, 18 million people are infected with Trypanosoma cruzi, the agent of Chagas' disease, with the greatest economic burden. Vertebrate calreticulins (CRT) are multifunctional, intra- and extracellular proteins. In the endoplasmic reticulum (ER) they bind calcium and act as chaperones. Since human CRT (HuCRT) is antiangiogenic and suppresses tumor growth, the presence of these functions in the parasite orthologue may have consequences in the host/parasite interaction. Previously, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(110 citation statements)
references
References 36 publications
3
103
0
4
Order By: Relevance
“…According to previous researches, some parasites have capability of antitumor activities (Darani and Yousefi 2012;Kim et al 2007;López et al 2010;Oikonomopoulou et al 2013;Pidherney et al 1993;Plumelle et al 1997) and so parasite antigens have been considered as possible targets for cancer immunotherapy (Darani and Yousefi 2012). In a retrospective study with a large population it has been shown that the prevalence of hydatid cysts in patients with cancer was significantly lower than the control group (Akgül et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous researches, some parasites have capability of antitumor activities (Darani and Yousefi 2012;Kim et al 2007;López et al 2010;Oikonomopoulou et al 2013;Pidherney et al 1993;Plumelle et al 1997) and so parasite antigens have been considered as possible targets for cancer immunotherapy (Darani and Yousefi 2012). In a retrospective study with a large population it has been shown that the prevalence of hydatid cysts in patients with cancer was significantly lower than the control group (Akgül et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are scientific evidences indicating that some parasitic and microbial infections interfere with tumor growth and have anticancer activities [1][2][3][4][5][6][7][8] , and it has been shown that some extracts of Trypanosoma cruzi have toxic effects on cancer cells in cell cultures [1,2]. Kim et al (2007) showed that Toxoplasma gondii inhibited Lewis lung carcinoma growth through induction of Th1 immune responses and inhibition of angiogenesis [3].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some parasitic infections induce antitumor activity against certain types of cancers [1][2][3][4][5][6]. We previously showed that mice immunized with Toxoplasma gondii tachyzoiter or Toxocara canis egg antigens and challenged with fibrosarcoma cells showed less solid tumor growth in comparison with mice that were not immunized but challenged with the same cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…14 Through a different domain, located in the amino terminal sequences, extracellular TcCRT interacts with endothelial cells, most likely through a collagen-like Scavenger-Receptor class A, because this interaction is inhibited by fucoidan, an homopolymer of sulfated L-fucose, 15 (Abello and others, 2014, unpublished). The interactions of TcCRT with endotheliocytes mediate antiangiogenic and antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of TcCRT with endotheliocytes mediate antiangiogenic and antitumor effects. [15][16][17] Monoallelic TcCRT KO parasites, the wild-type, and a transgenic variant (with an extra TcCRT gene copy), display increasing survival capacity in the presence of human complement, and enhanced in vivo infectivity (TcCRT homozygous KO parasites are not viable). 18,19 Parasite TcCRT location once the parasite is inside the mammal cell has not been reported, as well as its functional roles in those new locations.…”
Section: Introductionmentioning
confidence: 99%